Moth Diversity of Chhattisgarh State, India - Sambath, S.; Chandra, Kailash (Indian Forester, 2013)
The present work was an attempt to document diversity of moth fauna of Chhattisgarh for assessing the ecological stability of the areas, which are highly susceptible due to various anthropogenic activities and coal mines in particular. A total of 90 species of moths belonging to 79 genera, 15 families, 26 subfamilies under 10 superfamilies were identified and recorded.